Interleukin 10: Bridging the chasms in the immune landscape of multiple myeloma - Fernandes, Queenie; Ansari, Abdul W.; Makni-Maalej, Karama; Merhi, Maysaloun; Dermime, Said; Ahmad, Aamir; Uddin, Shahab (International review of cell and molecular biology, 2025)
[Display omitted] Multiple myeloma (MM) is a complex hematologic malignancy characterized by the abnormal proliferation of plasma cells in the bone marrow, leading to significant clinical challenges and a high burden of morbidity and mortality. Interleukin 10 (IL-10), a cytokine with potent anti-inflammatory properties, has emerged as a critical player in the pathobiology of MM. This work delves into the multifaceted role of IL-10 in MM, exploring its contributions to tumor growth, immune evasion, and drug resistance. Here, we examine IL-10’s interactions with various immune cells within the bone marrow microenvironment and its potential as a circulatory biomarker for MM. Furthermore, we particularly lay emphasis on the prognostic and diagnostic implications of IL-10 levels in MM patients and evaluate the therapeutic prospects of targeting IL-10 in MM treatment regimens. By synthesizing current research, this review aims to enhance the understanding of IL-10 as a circulatory biomarker in MM and to highlight novel avenues for therapeutic intervention, thereby translating to improved clinical outcomes for MM patient.